DETERMINASI ALGORITMA DAN POLARISASI OPINI PUBLIK: ANALISIS PERILAKU INFORMASI PADA TATA KELOLA PERPUSTAKAAN UMUM PROVINSI DKI JAKARTA - Muhammad Haikal; Zayyin Abdul Quddus; Hendika Dwinanda Wicaksana (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
ABSTRACT The transformation of digital technology has radically altered the patterns of public information behavior. Social media platforms no longer operate merely as transmission mediums, but as technological structures dictating the consumption of public discourse. This study aims to analyze the influence of recommendation system algorithmic determinism on the construction of public opinion polarization regarding governance metrics and access policies (the Jaklitera system) at the Jakarta Library. Through a literature review approach within information systems science, this study dissects how algorithmic engineering intervenes in the public's information encountering and receiving phases. The literature synthesis indicates that algorithms operate as conflict architects, constructing two isolated narrative bubbles through filter bubble and echo chamber mechanisms. Citizen information behavior is divided into a pro-order pole driven by civic fatigue, and a pro-accessibility pole that responds to policies as administrative repression, while institutional arguments regarding carrying capacity are organically shadowbanned. This phenomenon proves that urban governance issues have been distorted into social segregation due to information behavior dysfunction commodified by platform metrics. The implications of this study assert that to realize inclusive governance, public institutions must evaluate the resilience of their information system architectures against technological determinism that capitalizes on opinion fragmentation.